"They Gave Me Life": Motherhood and Recovery in a Tribal Community. (15th October 2018) - Schultz, Katie; Teyra, Ciwang; Breiler, Glenda; Evans-Campbell, Tessa; Pearson, Cynthia
ABSTRACT: Objective: This study explored factors related to substance misuse and recovery among Native mothers in a Pacific Northwest tribe, focusing on motherhood as a motivating factor in seeking treatment and sustaining recovery. Method: Using a community-based participatory research approach, we conducted a thematic analysis of 20 in-depth interviews and one focus group (N = 12) with Native women 18 years and older living on or near the reservation. Results: Qualitative findings highlighted challenges, motivations and strategies for seeking treatment and recovery in four major themes: (a) the close relationship between interpersonal violence and substance misuse; (b) traditional healing in recovery; (c) community-specific challenges to recovery; and (d) the motivating role of motherhood in seeking treatment and successful recovery. Conclusions: A central finding of this work is that pregnancy and motherhood may be underexplored factors in Native women's substance use. Results support previous work suggesting that Native women are at high risk of interpersonal trauma and that trauma contributes to substance misuse. Findings offer several rich implications for treatment and recovery among Native mothers in tribal communities including the necessity of trauma-informed treatment, community and culturally-based interventions, more integration of treatment services with Child Protective Services, and drawing on motherhood as a motivation for seeking and succeeding in recovery.